KEANEKARAGAMAN HASIL TANGKAPAN MENGGUNAKAN ALAT TANGKAP TRAWL MINI (Mini Bottom Trawl) DI KELURAHAN KAMPUNG NELAYAN KECAMATAN TUNGKAL ILIR - Febi Lestari; Nurhayati Nurhayati; M Hariski; Fauzan Ramadan; Yun Alwi; Raguati Raguati (JURNAL AKUAKULTUR, TEKNOLOGI DAN MANAJEMEN PERIKANAN TANGKAP, ILMU KELAUTAN, 2025)
Mini trawl fishing gear has a positive impact as a source of livelihood, but it also has a negative impact on marine biodiversity due to its non-selective nature. This condition requires wise management of aquatic resources in maintaining the sustainability of the marine ecosystem, especially in the waters of Kampung Nelayan Village. The purpose of this study is to determine the diversity of catches in Mini Trawl fishing gear (Mini bottom trawl) in Kampung Nelayan Village, Tungkal Ilir District, Tanjung Jabung Barat Regency. The research method used is the survey method, a method of determining respondents using simple random sampling of 10% from 50 people to 5 fishermen for 10 arrests. The data analysis used was the Diversity Index, Uniformity Index and Dominance Index. The results of the study were obtained that the diversity index value of 3.19 was included in the high category (H'>3), the uniformity index of 1.06 was included in the high category (E>0.6), and the dominance index of 0.06 was included in the low category (C'<0.4). The conclusion of this study is that the value of the diversity index is high, uniformity is high and no species dominate